Human Resource Development Management (Study at Adonara Timur Senior High School, Distict of Flores Timur, Nusa Tenggara Timur - Indonesia) (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study is to find out how the planning, implementation and results of the implementation of human resource development management in senior high school (SMA Negeri I) Adonara Timur, distric of Flores Timur. This study used qualitative research methods. The collection technique is done by observation or observation, interview, and documentation study. The process of data analysis is carried out before data is obtained and during data collection is done (data reduction). The inherent oddities are re-verified in the presentation of the data and then the final conclusion is found to be fundamental. The conclusion of the research is the implementation of human resource development management in SMA Negeri I Adonara Timur implemented by passing the stages in management, namely: planning, organizing, implementation, and supervision. Planning is implemented by the school leadership by making regular observations to all of his subordinates. Thus, from these observations the leadership can determine what needs are needed and what development programs are needed in an effort to improve the quality of education in SMA Negeri I Adonara Timur. Implementation of human resource development program in SMA Negeri I Adonara Timur has been going on and on continuously. Implementation of human resource development in SMA Negeri I Adonara Timur is through training and education, concretely implemented in the form of activities such as curriculum socialization, upgrading, workshops, training, panel discussions, scientific discussions, and the existence of the plan of study program continued for certain teachers. Implementation of these programs on a regular basis and is mandatory and received direct supervision from the leadership. 3) Implementation of human resource development in SMA Negeri I Adoara Timur produce results in accordance with the targeted. The results are measured by the high percentage of graduation as well as the high percentage in the selection of admissions at state universities at provincial and national levels.